IoT Optical-based Health Monitoring System for Portable Vital-sign Measurement - MOHD ESOOP, AL FAJIR (IRC, 2019)
“The mobile device is becoming a significant part of everyday life in this millennial era. The health monitoring and disease diagnosing have been greatly improvised by revolutionary approach of skin-based wearable. Wireless optical based sensor or portable skin-based wearable which monitors wearer’s health is an example of these technologies which holds real-time biometric data which can help the physician in treating patients disease at an earlier stage. This portable health monitoring technology have great potential in revolutionizing the approach of medical treatment due its convenient function of real-time and data logging of biometric data in cloud to accessed by physician from anywhere with the necessary permissions. Although this technology is more focussed on monitoring health of elderly people, the younger one would also benefits from this portable technology due to the crucial health information could be obtained in case of emergency where the wearer is in no position to discuss about her health condition. This paper will discuss on development of working prototype of wearable pulse rate sensors with green LED interconnected with a mobile application via Wi-Fi which will autonomously update pulse rate through internet periodically. In addition, this pulse data will be also logged to cloud where the user can access the past vital-sign measurement of the wearer. The project aims to create a common platform as a place to communicate physician and patient regardless of age where physician can monitor the patient’s daily pulse data.”